Rethinking historicism from Shakespeare to Milton - Coiro, Ann Baynes; Fulton, Thomas (Cambridge : Cambridge University Press, 2012)
"Reading literary texts in their historical contexts has been the dominant form of interpretation in literary criticism for the past thirty years. This collection of essays reflects on the origins of historicism and its present usefulness as a mode of literary analysis, its limitations, and its future. The volume provides a brief history of the practice from its renaissance origins, offering examples of historicist work that not only demonstrate the continuing vitality of this methodology but also suggest new directions for research. Focusing on the major figures of Shakespeare and Milton, these essays provide important and concise representations of trends in the field. Designed for scholars and students of early modern English literature (1500-1700), the volume will also be of interest to students of literature more generally and to historians"--
Has historicism gone too far, or, Should we return to form? / Andrew Hadfield -- Theory and practice in historical method / Michael McKeon -- Limiting history / Marshall Grossman -- The politics of Renaissance historicism : Valla, Erasmus, Colet, and More / Thomas Fulton -- Historicizing satisfaction in Shakespeare's Othello / Heather Hirschfeld -- The new presentism and its discontents : listening to Eastward ho and Shakespeare's Tempest in dialogue / Paul Stevens -- In great men's houses : playing, patronage, and the performance of Tudor history / Lawrence Manley -- Medea's dilemma : politics and passion in Milton's Divorce tracts / Sharon Achinstein -- Milton, Foucault, and the new historicism / Martin Dzelzainis -- You shall be our generalless : fashioning warrior women from Henrietta Maria to Hillary Clinton / Laura Knoppers -- War times : seventeenth-century women's writing and its afterlives / Erin Murphy
Includes bibliographical references and index.
Keywords: Historical criticism (Literature); New historicism; English literature -- Early modern, 1500-1700 -- History and criticism -- Theory, etc; LITERARY CRITICISM / European / English, Irish, Scottish, Welsh